2021
DOI: 10.3389/fpls.2021.776939
|View full text |Cite
|
Sign up to set email alerts
|

γ-Aminobutyric Acid (GABA) Priming Improves Seed Germination and Seedling Stress Tolerance Associated With Enhanced Antioxidant Metabolism, DREB Expression, and Dehydrin Accumulation in White Clover Under Water Stress

Abstract: As an important plant growth regulator, the role of γ-aminobutyric acid (GABA) in regulating seeds germination was less well elucidated under water stress. The present study was conducted to investigate the impact of GABA pretreatment on seeds germination of white clover (Trifolium repens) under water deficient condition. Results demonstrated that seeds pretreated with 2μmol/l GABA significantly alleviated decreases in endogenous GABA content, germination percentage, germination potential, germination index, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 81 publications
2
15
0
3
Order By: Relevance
“…It has been well documented that plants may accumulate compatible solutes, such as carbohydrates and amino acids, which are energy source, osmotic regulants, as well as signaling molecules under saline conditions [ 3 , 4 ]. Among these stress-responsive metabolites, γ-aminobutyric acid (GABA) is of special interest since its anabolic metabolism could be activated by salt stress, and it has been observed to be accumulated rapidly in the plants under salt stress [ 5 , 6 , 7 , 8 ]. Previous studies have demonstrated that GABA has an important effect on plant salt tolerance as a signal substance or temporary nitrogen pool, or as a regulator to cytoplasmic pH and antioxidant responses [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been well documented that plants may accumulate compatible solutes, such as carbohydrates and amino acids, which are energy source, osmotic regulants, as well as signaling molecules under saline conditions [ 3 , 4 ]. Among these stress-responsive metabolites, γ-aminobutyric acid (GABA) is of special interest since its anabolic metabolism could be activated by salt stress, and it has been observed to be accumulated rapidly in the plants under salt stress [ 5 , 6 , 7 , 8 ]. Previous studies have demonstrated that GABA has an important effect on plant salt tolerance as a signal substance or temporary nitrogen pool, or as a regulator to cytoplasmic pH and antioxidant responses [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this process, α-ketoglutarate takes glutamate as a substrate, forms GABA in mitochondria under the catalysis of glutamate decarboxylase (GAD), then converts into succinic semialdehyde (SSA) under the catalysis of GABA transaminase (GABA-T) and finally is converted to succinic acid by SSA dehydrogenase (SSADH), which is added to the TCA cycle or is transported back to the cytoplasm [ 12 , 13 , 14 ]. Among the GABA shunt enzymes, GAD is the most sensitive one in response to abiotic stress, and its gene expression and enzyme activity levels are closely associated with the enhancement of plant stress resistance mediated by GABA [ 6 , 15 , 16 ]. In wheat ( Triticum aestivum ), tobacco ( Nicotiana sylvestris ), melon ( Cucumis melo ) and other plants, the expression levels of GAD genes were significantly enhanced under salt stress, resulting in the increase in GABA content and high salt tolerance [ 7 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Seed priming with bioactive compounds or elements such as zinc, γ-aminobutyric acid (GABA), putrescine (Put), diethyl aminoethyl hexanoate (DA-6), or spermidine (Spd) has been proven as an effective way to improve seed germination under normal and stressful conditions [ 19 , 20 , 21 , 22 , 23 ]. Previous studies have found that chitosan-black soybean seed-coat extract exhibited strong antioxidant property, and CTS coating could effectively improve seed germination, seedling growth, and resistance to pests under normal condition [ 24 , 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…ABA‐dependent transcription factor ABFs up‐regulated expressions of defensive genes such as dehydrins ( DHNs ) or late embryogenesis abundant proteins ( LEAs ) by binding to ABA response elements ( ABREs ) in promoters of these defensive genes, which was one of important ABA‐regulatory mechanisms of cold tolerance in plants (Heidarvand & Amiri, 2010). DHNs or LEAs are essential for plants to cope with drought, salt stress, and cold stress due to their positive functions of ROS scavenging, protein protection, and anti‐dehydration in cells (Cheng et al., 2018; Vaseva et al., 2014; Zhou et al., 2021). Exogenous ABA pretreatment effectively enhanced chilling tolerance of bermudagrass through up‐regulating ABF1 expression (Cheng et al., 2016).…”
Section: Discussionmentioning
confidence: 99%